Chiral 1, 3, 2‐Diazaphospholenes as Catalytic Molecular Hydrides for Enantioselective Conjugate Reductions. Issue 15 (6th March 2018) - Miaskiewicz, Solène; Reed, John H.; Donets, Pavel A.; Oliveira, Caio C.; Cramer, Nicolai
Abstract: Secondary 1, 3, 2‐diazaphospholenes have a polarized P−H bond and are emerging as molecular hydrides. Herein, a class of chiral, conformationally restricted methoxy‐1, 3, 2‐diazaphospholene catalysts is reported. We demonstrate their catalytic potential in asymmetric 1, 4‐reductions of α, β‐unsaturated carbonyl derivatives, including enones, acyl pyrroles, and amides, which proceeded in enantioselectivities of up to 95.5:4.5 e.r. Abstract : Strong backbone : A class of chiral 1, 3, 2‐diazaphospholenes with rigidified backbones has been developed. In first benchmark experiments, they are shown to behave as catalytic molecular hydrides for enantioselective 1, 4‐reductions.